ASPP2 Plays a Dual Role in gp120-Induced Autophagy and Apoptosis of Neuroblastoma Cells - Liu, Zhiying; Qiao, Luxin; Zhang, Yulin; Zang, Yunjing; Shi, Ying; Liu, Kai; Zhang, Xin; Lu, Xiaofan; Yuan, Lin; Su, Bin; Zhang, Tong; Wu, Hao; et al. (Frontiers in Neuroscience, 2017)
HIV invasion of the central nervous system (CNS) in the majority of patients infected with HIV-1, leads to dysfunction and injury within the CNS, showing a variety of neurological symptoms which was broadly termed HIV-associated neurocognitive disorder (HAND). But the molecular mechanisms are not completely understood. It has been suggested that apoptosis and autophagic dysfunction in neurons may play an important role in the development of HAND. Previous studies have indicated that p53 may be involved in the onset of neurological disorder in AIDS. Apoptosis-stimulating protein of p53-2 (ASPP2), a p53-binding protein with specific function of inducing p53, has been reported to modulate autophagy. In the present study, we observed that gp120 induces autophagy and apoptosis in SH-SY5Y neuroblastoma cells. Adenovirus-mediated overexpression of ASPP2 significantly inhibited autophagy and apoptosis induced by low dose of gp120 protein (50ng/mL), but induced autophagy and apoptosis when treated by high dose of gp120 protein (200ng/ mL).Further, ASPP2 knockdown attenuated autophagy and apoptosis induced by gp120. Conclusion: ASPP2 had different effects on the autophagy and apoptosis of neurons induced by different concentration of gp120 protein. It may be a potential therapeutic agent for HAND through modulating autophagy and apoptosis in CNS.